Observations of Turbulent Heat Fluxes Variability in a Semiarid Coastal Lagoon (Gulf of California) - Lidia Irene Benítez-Valenzuela; Zulia Mayari Sanchez-Mejia (Atmosphere, 2020)
Despite the critical role latent (LE) and sensible (H) heat play in turbulent processes and heat exchange in the water–air interface, there is a lack of studies of turbulent fluxes over the surface in semiarid regions. We collected continuous measurements of net radiation (Rn), LE, H, and micrometeorological data at a coastal lagoon in the Gulf of California during 2019 with an eddy covariance (EC) system. We analyzed the time series, considering the North American Monsoon System, the pre-monsoon, and post-monsoon season. Results show that Rn (276 ± 118 W m−2) and turbulent fluxes were higher during the monsoon season (July–September) LE (129 ± 18 W m−2), and H (29 ± 9 W m−2). The monthly average of Rn, LE, and H was highest in June (493.9 W m−2), August (142 W m−2), and May (50 W m−2), respectively. Furthermore, during the monsoon season, the (H + LE)/Rn ratio (0.74) suggests that more than half of the Rn reaching the coastal lagoon is used for the turbulent exchange of LE and H. During the pre-monsoon, LE (r2 = 0.36) increases with a higher vapor pressure deficit (VPD), while H (r2 = 0.66) increases with a higher friction velocity (u*) during the monsoon season. Quantitative observations are essential for further research.